Happiness and productivity - Andrew J. Oswald; Eugenio Proto; Daniel Sgroi (Institute for the Study of Labor (IZA), 2009)
The paper provides evidence that happiness raises productivity. In Experiment 1, a randomized trial is designed. Some subjects have their happiness levels increased, while those in a control group do not. Treated subjects have 12% greater productivity in a paid piece-rate Niederle-Vesterlund task. They alter output but not the per-piece quality of their work. To check the robustness and lasting nature of this kind of effect, a complementary Experiment 2 is designed. In this, major real-world unhappiness shocks - bereavement and family illness - are studied. The findings from (real-life) Experiment 2 match those from (random-assignment) Experiment 1.
Keywords: D03; J24; C91; 330; Labor productivity; emotions; well-being; happiness; positive affect; experimental economics; Lebenszufriedenheit; Arbeitsproduktivität; Test; Großbritannien